2016
DOI: 10.1111/tan.12787
|View full text |Cite
|
Sign up to set email alerts
|

Expression of classical HLA class I molecules: regulation and clinical impacts

Abstract: Human leukocyte antigen (HLA) class I genes are ubiquitously expressed, but in a tissue specific-manner. Their expression is primarily regulated at the transcriptional level and can be modulated both positively and negatively by different stimuli. Advances in sequencing technologies led to the identification of new regulatory variants located in the untranslated regions (UTRs), which could influence the expression. After a brief description of the mechanisms underlying the transcriptional regulation of HLA cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 106 publications
0
25
0
1
Order By: Relevance
“…The products of these alleles have different immunological functions based on their ability to present specific peptides to cytotoxic T lymphocytes and bind various KIR ligands on NK cells, and their expression levels can extensively affect biological and pathological processes. 1 It has been confirmed that the expression levels of different alleles on the same HLA class I locus can vary dramatically. [2][3][4][5][6] This differential HLA expression according to alleles could have a broad clinical impact, such as influencing virus infection control, 4,7 risk of autoimmune disorders, 4,[8][9][10] and haematopoietic stem cell transplantation (HSCT) outcomes.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The products of these alleles have different immunological functions based on their ability to present specific peptides to cytotoxic T lymphocytes and bind various KIR ligands on NK cells, and their expression levels can extensively affect biological and pathological processes. 1 It has been confirmed that the expression levels of different alleles on the same HLA class I locus can vary dramatically. [2][3][4][5][6] This differential HLA expression according to alleles could have a broad clinical impact, such as influencing virus infection control, 4,7 risk of autoimmune disorders, 4,[8][9][10] and haematopoietic stem cell transplantation (HSCT) outcomes.…”
Section: Introductionmentioning
confidence: 95%
“…More than 10 000 alleles on HLA‐A, ‐B, and ‐C loci have been revealed in human populations. The products of these alleles have different immunological functions based on their ability to present specific peptides to cytotoxic T lymphocytes and bind various KIR ligands on NK cells, and their expression levels can extensively affect biological and pathological processes …”
Section: Introductionmentioning
confidence: 99%
“…It must be emphasized that the regulation of MHC class I gene expression by these hormones and growth factors involves the binding of NF-κB dimers to the enhancer A region of the MHC class I promoter (Figure 2 ). The enhancer A region is located in a “hormone-sensitive region” of the MHC class I promoter (i.e., −500 to −68 bp), and this region is responsible for the regulation of MHC class I expression by hormones, cytokines, chemokines, and drugs ( 33 , 35 , 40 ). The enhancer A sequence (5′-GGGGAGTCCCC-3′) that spans nucleotides −180 bp to −170 bp is a palindromic variant of the κB consensus site, and it can bind NF-κB dimers ( 43 ).…”
Section: Nf-κb and The Thyroidmentioning
confidence: 99%
“…HLA expression is also impacted by 5 ′ and 3 ′ UTR containing, e.g. promoter and microRNA binding sites (12)(13)(14). Variation in these sites has been observed, e.g.…”
Section: Introductionmentioning
confidence: 99%